An investigation of photo-double ionization in benzene. Issue 10 (January 2020) - Howard, J; Sokell, E; Bolognesi, P; Avaldi, L
Synopsis: A photo-double ionization (PDI) coincidence technique has been used to study electron correlation as a function of photon impact energy on Benzene (C6 H6 ). The simultaneous emission of two photoelectrons from the benzene π orbital has been measured using two sets of hemispherical electron energy analysers. Angle resolved single and coincidence photoelectron spectra are reported, providing new data on the PDI mechanism.